BCL2 and BCLxL are key determinants of resistance to antitubulin chemotherapeutics in melanoma cells. Issue 8 (27th June 2013) - Watanabe, Ayano; Yasuhira, Shinji; Inoue, Tsuyoshi; Kasai, Shuya; Shibazaki, Masahiko; Takahashi, Kazuhiro; Akasaka, Toshihide; Masuda, Tomoyuki; Maesawa, Chihaya
Abstract: Malignant melanoma is refractory to various chemotherapeutics including antitubulin agents such as paclitaxel. Previous studies have suggested a link between βIII‐tubulin overexpression and paclitaxel resistance through alterations in the properties of the mitotic spindle. We found that paclitaxel treatment induced temporary mitotic arrest in 7 melanoma cell lines irrespective of the βIII‐tubulin level, suggesting that βIII‐tubulin had no significant influence on spindle properties. On the other hand, the amount of BCL2, an anti‐apoptotic protein, was well correlated with paclitaxel resistance. Treatment of the paclitaxel‐resistant cell lines with ABT‐737, an inhibitor of BCL2 and BCLxL, or simultaneous knock‐down of BCL2 and BCLxL dramatically increased the cells' sensitivity, while knock‐down of MCL1, another member of the BCL2 family, had only a minimal effect. Our results suggest that the paclitaxel sensitivity of melanoma cells is attributable to apoptosis susceptibility rather than a change in spindle properties and that BCL2 and BCLxL play a pivotal role in the former.